Breaking Down Stereotypes: A Critical Discourse Study of Sexism in English Textbooks - Habibah, Sa’idatul; Basya, Dihliza (Universitas Negeri Semarang, 2024)
This study aims to critically examine and deconstruct gender stereotypes embedded and hidden within the EFL textbook. Through analyzing various visual images and illustration, this study will focus on identifying benevolent and hostile sexist values (Glick & Fiske, 1996) within the newly published autonomous curriculum EFL textbook. In doing so, Critical Discourse Analysis (Fairclough, 2003) will be employed in order to unearth hidden biases and depict the representativeness of each gender based on benevolent and hostile sexist values. Meanwhile, to analyze the hidden value within visual images, this study employs visual grammar theory (Kress & Van Leeuwen, 2021) and textual analysis (Halliday., 1978). The findings of this study indicate that EFL textbooks effectively incorporate sexism values against gender stereotypes, including Benevolent and Hostile sexism (Glick & Fiske, 1996), consistently throughout the visual and verbal text. Both visual and verbal texts illustrate how these values are integrated into current topics that are associated with gender stereotypes in the form of prejudice contained in EFL textbooks. The implication of this study is a more concrete application for improving educational materials and practices by trying to represent gender stereotypes in EFL textbooks towards ELT. The results of this study will hopefully become empirical evidence within the huge body of gender representation studies. Additionally, the result of this study will hopefully provide valuable insight for students, teachers, and curriculum developers, and broaden their outlooks concerning the hidden benevolent and hostile sexist values within the EFL textbook.